Detection of unobserved heterogeneity with growth mixture models - Reinecke, Jost (2009)
Latent growth curve models as structural equation models are extensively discussed in various research fields (Duncan et al., 2006). Recent methodological and statistical extension are focused on the consideration of unobserved heterogeneity in empirical data. Muth´en extended the classical structural equation approach by mixture components, i. e. categorical latent classes (Muth´en 2002, 2004, 2007). The paper will discuss applications of growth mixture models with data from one of the first panel studies in Germany which explore deviant and delinquent behavior of adolescents (Reinecke, 2006a, 2006b). Observed as well as unobserved heterogeneity will be considered with growth mixture models using the program Mplus (Muth´en & Muth´en, 2006). Special attention is given to the distribution of the substantivedependent variables as a count measures (Poisson distribution, zero-inflated Poisson distribution, cf. Nagin, 1999). Different model specifications with respect to substantive questions will also be emphasized.